PENERAPAN MODEL PEMBELAJARAN CONCEPT SENTENCE DALAM MATERI MENULIS PUISI PADA SISWA KELAS V DI SEKOLAH DASAR - Supriyadi Nursalam (MEDIA DIDAKTIKA, 2020)
The study, entitled Application of the Concept Sentence Learning Model in Poetry Writing Materials for Class V Students in Elementary Schools, was motivated by learning that provided opportunities for students to actively learn by changing student-centered learning models. The purpose of this study is to describe: (1) student learning skills, (2) student activities, (3) student responses, and (4) teacher activities. This research was carried out at MI Darul Ulum, Wudi village, Sambeng district, Lamongan regency. The subject of this research was the fifth grade students totaling 20 students. The data taken from this study were data about the implementation of the concept sentence learning model on poetry writing material. Data collection techniques used are observation, tests and questionnaires. The observation method is used to find out the activities of students and teachers during the learning process. The test method is used to determine the level of student learning completeness individually or classical after the concept sentence learning model is carried out. The questionnaire method is used to find out the student's response to the learning that has been done. Based on the research, it is known that the application of effective concept sentence learning models applied to Indonesian language learning poetry writing material in fifth grade elementary schools, especially the Darul Ulum MI in Wudi Village, Sambeng District, Lamongan Regency, in terms of several things, among others; (1) learning completeness of 90% of students was declared complete, while 10% of students still needed to need guidance to make poetry. (2) percentage of student activities, amounting to 93.80% of students have positive activities in learning, while 6.20% of students still behave not in accordance with learning. (3) positive response from students, 89% of students responded very happy, 10% of students responded happily, and 1% of students responded unhappy. (4) the teacher's response, 86.25% of the teacher's positive activities are very supportive in the learning process, while 13.75% there are teacher activities that are not related to the learning process.